Analytical assessment of legal translation: a case study using the American Translators Association framework - Mary Phelan (JoSTrans: The Journal of Specialised Translation)
A number of analytical grading systems for translation have been developed since the 1970s. The objective of the case study described in this article was to establish the suitability of that of the American Translators Association (ATA), to assessment of a legal translation. To this end, a judgment from the English court of appeal was translated into Spanish by a Translation Studies student. Ten assessors, all of whom were experienced translators and native speakers of Spanish and two of whom were also experienced ATA graders, applied the ATA framework for standardised error marking and the associated flowchart for error point decisions to the translation. Under this negative marking system, candidates must score under 18 points to pass. The subjective element in terms of decision making was such that assessors allocated total marks of between 9 and over 45 to the translation with three passing and seven failing the translation. Despite these results, in their feedback six assessors deemed the translation acceptable for professional purposes while four felt that it was unacceptable. Assessor feedback indicated that some error categories overlapped or were vague while the flowchart was difficult to implement, in particular when deciding the level of seriousness of errors.